2007
DOI: 10.1159/000106583
|View full text |Cite
|
Sign up to set email alerts
|

Thalidomide in the Treatment of Kaposi’s Sarcoma

Abstract: Background: Kaposi’s sarcoma (KS) is a lymphangioproliferative tumour. Therapy of KS depends on the characteristics of the disease, especially area and growth rate of lesions, and patient condition. Currently symptomatic resectable lesions are excised, whereas more advanced disease and unresectable lesions are treated with radiotherapy. If a large area or internal organs are affected or other treatments fail, chemotherapy is used. Recently some authors have reported their encouraging experience in the use of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
0
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 38 publications
0
12
0
1
Order By: Relevance
“…In both HIV and non-HIV associated KS there is evidence that oral thalidomide at 3 mg/kg every evening for 4 months leads to a reduction in the number and size of skin nodules, reduces oedema and improves appetite and general wellbeing when measured by the Lansky score. It is given in the evening because it may make patients drowsy [32]. In Malawi, 49 HIV-infected ART-naive children with KS were given thalidomide for 4 months: 75% responded with tumour reduction and an improved Lansky score of whom 90% maintained a good response for 6 months [33].…”
Section: Treatment Regimensmentioning
confidence: 99%
“…In both HIV and non-HIV associated KS there is evidence that oral thalidomide at 3 mg/kg every evening for 4 months leads to a reduction in the number and size of skin nodules, reduces oedema and improves appetite and general wellbeing when measured by the Lansky score. It is given in the evening because it may make patients drowsy [32]. In Malawi, 49 HIV-infected ART-naive children with KS were given thalidomide for 4 months: 75% responded with tumour reduction and an improved Lansky score of whom 90% maintained a good response for 6 months [33].…”
Section: Treatment Regimensmentioning
confidence: 99%
“…Taken together, these results suggest that thalidomide is not a major therapy for KS, with a disappointing response rate and limitations due to side-effects, although it could be useful in some specific cases as shown by Rubegni et al [9] . However, an anti-angiogenic approach may still be interesting in KS, as suggested by Ben M'barek et al [10] .…”
mentioning
confidence: 63%
“…retrospective studies [9,10] . In the first study, Rubegni et al [9] treated 3 patients with 100 mg/day of thalidomide for 1 year and observed a complete response in 2 patients (including an immunosuppressed patient with systemic KS) and a partial response in the third.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…59,60 In a prospective, open-label, phase II clinical trial using imiquimod 5% cream to treat KS, eight of 17 patients showed clinical improvement of the lesions. 60 Rubegni et al 61 reported the treatment of three non-AIDS relatedeKS patients with thalidomide 100 mg/day. All experienced partial remission at 4 months, and two patients achieved complete remission at 12 months.…”
Section: Cutaneous Lymphoma Key Points Dmentioning
confidence: 99%